Increasing awareness of the dangers of vaping for students at Rossville Junior/Senior High School - Welshans, Nicole (My University, 2020)
Teen vaping has increased steadily for many years, quickly rising to epidemic levels. Products are becoming more readily available and being marketed to school-aged kids. The need for education on the dangers of vaping has never been greater. This project addressed the struggles with vaping at Rossville Junior/Senior High School in Rossville, Kansas. A needs assessment was completed as a self-reported survey to determine the extent of interventions needed at this school. Concurrently, an anti-vaping campaign was launched at an all-school assembly. The goal of the assembly was to reach a large number of students with accurate information regarding the dangers of vaping. Following the assembly, student volunteers created educational posters to reinforce the dangers of vaping. Additionally, metal signs from the Kansas Department of Health and Environment will be ordered and later posted throughout the school in strategic areas. The current school policy regarding vaping was reviewed, and a new policy was proposed (to administrators) to address its deficiencies. The new proposed policy is more universal in scope, removing clauses that were open to interpretation by different school clubs and teams. In addition, an interactive educational product was created for the school. It was designed to be used as a remediation tool for students who violate the new policy prior to being readmitted to school from their consequence. All components of the anti-vaping campaign will be permanent integrations at Rossville Junior/Senior High School. A future goal is to expand the anti-vaping campaign to include more students who expressed interest in helping. Positive student involvement is critical in reaching at-risk students.
Keywords: at-risk students; vaping risks